Identifikasi Serangga Hama pada Tanaman Metimun di Desa Bumi Agung, Kecamatan Lempuing, Kabupaten Ogan Komering Ilir, Sumatera Selatan - Arsi Arsi; Hendra Hendra; Suparman SHK; Yulia Pujiastuti; Siti Herlinda; Harman Hamidson; B. Gunawan; Chandra Irsan; Suwandi Suwandi; R Anwar Efendi; S Imam Nugraha; Lailaturrahmi Lailaturrahmi; R Putra Munandar (xxxx-xxxx, 2020)
Arsi A, Hendra H, Suparman SHK, Pujiastuti Y, Herlinda S, Hamidson H, Gunawan B, Irsan C, Suwandi S, Efendi RA, Nugraha SI, Lailaturrahmi L, Munandar RP. 2020.  Pest insect identification on cucumber plants in Bumi Agung village, Lempuing district, Ogan Komering Ilir regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The cultivation of vegetable crops is very much practiced by farmers both in the highlands and in the lowlands. In the cultivation of vegetables, pests and diseases cannot be separated. Pests that attack cucumber plants can be detrimental both in quality and quantity. The purpose of this study was to determine the insect pests that attack cucumber plants. Observations were made by comparing 2 cucumber fields. The comparison of the 2 fields was then carried out using the t test method. The results of observations on cucumber plants in the field were 4 species of insect pests that attack cucumber plants. Insects that attack cucumber plants consist of Diaphania sp., Aulacophora similis, Bemisia tabaci and Liriomyza sp.. The population of insect pests was found only 3 species based on visual observation and the intensity of pest attacks on cucumber plants was found to be 4 species of insect pests that attack these plants. In the t test results on insect populations, the species of Bemisia tabaci were significantly different in land 1 and land 2, while Diaphania sp. And A. Similis is not real different. The intensity of insect pests of Diaphania sp., Aulacophora similis and Liriomyza sp. Unreal different. However, the intensity of the Bemisia Tabaci attack was significantly different. The intensity of insect pests attack on land 1 was 44.76%, while on land 2 was 42.97%. Cultivation of cucumber with technical culture affects insect pests and the intensity of pest attacks.